2016
DOI: 10.1042/bst20160170
|View full text |Cite
|
Sign up to set email alerts
|

PHLPPing through history: a decade in the life of PHLPP phosphatases

Abstract: In the decade since their discovery, the PH domain Leucine rich repeat Protein Phosphatases (PHLPP) have emerged as critical regulators of cellular homeostasis and their dysregulation is associated with various pathophysiologies, ranging from cancer to degenerative diseases such as diabetes and heart disease. The two PHLPP isozymes, PHLPP1 and PHLPP2, were identified in a search for phosphatases that dephosphorylate Akt, and thus suppress growth factor signaling. However, given that there are over 200,000 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 56 publications
0
83
0
Order By: Relevance
“…We have earlier demonstrated that the Pleckstrin homology domain and leucine‐rich repeat protein phosphatase 1 (PHLPP1), which directly dephosphorylates and inactivates Akt‐2, is a downstream target of CB 1 R for inducing insulin resistance in DIO mice . mTORC2 and PHLPP1 have been recently identified as part of a regulatory complex for chaperone‐mediated autophagy where they serve opposite—stimulatory and inhibitory—functions .…”
Section: Discussionmentioning
confidence: 99%
“…We have earlier demonstrated that the Pleckstrin homology domain and leucine‐rich repeat protein phosphatase 1 (PHLPP1), which directly dephosphorylates and inactivates Akt‐2, is a downstream target of CB 1 R for inducing insulin resistance in DIO mice . mTORC2 and PHLPP1 have been recently identified as part of a regulatory complex for chaperone‐mediated autophagy where they serve opposite—stimulatory and inhibitory—functions .…”
Section: Discussionmentioning
confidence: 99%
“…As an identified tumor suppressive gene, multiple lines of evidence reveal the role of PHLPP2 in tumor progression . PHLPP2 is involved in the inhibition of malignant behaviors of cancer attributed to the suppression of prosurvival signaling such as through the PI3K/Akt signaling pathway . In addition, PHLPP2 can dephosphorylate and stabilize the Myc oncogene to suppress the progression of prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…PHLPP2 regulates several cellular pathways in cancer . Notably, direct dephosphorylation by PHLPP2 inactivates pro‐oncogenic AGC kinases such as Akt, S6K, and PKC and activates pro‐apoptotic kinases such as Mst1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies indicate that PHLPP1 and PHLPP2 may both serve as tumor suppressors, largely attributed to PHLPP-dependent suppression of pro-survival signaling, such as through the PI3K/ Akt signaling pathway [37,46]. The phosphatidylinositol-3 kinase (PI3K) signaling pathway plays an essential role in some physiological and cellular processes including cell proliferation, growth, survival, migration, and metabolism [47].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%